2018
DOI: 10.1029/2018ja025990
|View full text |Cite
|
Sign up to set email alerts
|

Alfvénic Heating in the Cusp Ionosphere‐Thermosphere

Abstract: The effect of electromagnetic variability on cusp‐region ionosphere‐thermosphere heating is examined. The study is motivated by observed correlations between anomalous thermospheric density enhancements at F region altitudes and small‐scale field‐aligned currents, previously interpreted as evidence of ionospheric Alfvén resonator modes. Height‐integrated and height‐dependent heating rates for Alfvén waves incident from the magnetosphere at frequencies from 0.05 to 2 Hz and perpendicular wavelengths from 0.5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 37 publications
7
40
0
Order By: Relevance
“…The Joule heating rate, which is treated as the sum of ion to neutral heat transfer and frictional heating rates, is shown in Figure 18c. It can be seen that the GITM-HIME Lotko and Zhang (2018) found the heating due to variability (66 mV/m) around 10 nW/m −3 and due to a quasi-static field (similar to our GITM-HIME[B] approach) around 38 nW/m −3 higher than the simulated response with a Weimer type electric field at the same altitude. Overall, the GITM-HIME[V] and GITM-HIME[T] rates produce three peaks at 0632, 0707, and 0742 UT.…”
Section: Evaluation Of Ion To Neutral Energy Transport Termssupporting
confidence: 73%
See 1 more Smart Citation
“…The Joule heating rate, which is treated as the sum of ion to neutral heat transfer and frictional heating rates, is shown in Figure 18c. It can be seen that the GITM-HIME Lotko and Zhang (2018) found the heating due to variability (66 mV/m) around 10 nW/m −3 and due to a quasi-static field (similar to our GITM-HIME[B] approach) around 38 nW/m −3 higher than the simulated response with a Weimer type electric field at the same altitude. Overall, the GITM-HIME[V] and GITM-HIME[T] rates produce three peaks at 0632, 0707, and 0742 UT.…”
Section: Evaluation Of Ion To Neutral Energy Transport Termssupporting
confidence: 73%
“…Figure 19 illustrates the altitude profile of the total ion to neutral volumetric energy transfer (Joule heating) rates obtained from the simulations. It can be seen that the GITM-HIME Lotko and Zhang (2018) found the heating due to variability (66 mV/m) around 10 nW/m −3 and due to a quasi-static field (similar to our GITM-HIME[B] approach) around 38 nW/m −3 higher than the simulated response with a Weimer type electric field at the same altitude. The simulated values at F region altitudes follow a similar trend; however, the magnitudes are very low due to nighttime electron densities to be compared directly.…”
Section: Evaluation Of Ion To Neutral Energy Transport Termssupporting
confidence: 73%
“…This energy input provides structured electric fields that can be of similar magnitude to those electrostatic features described earlier (Keiling et al, 2019). They do not affect the bulk circulation of the plasma in the ionosphere but selectively heat the I-T in the upper region due to the resonant trapping of Alfvén waves by the plasma density gradient in the topside ionosphere (e.g., Lotko & Zhang, 2018;Verkhoglyadova et al, 2018). Alfvénic energy sources need to be identified in a systematic way to be incorporated into models of the I-T behavior since they represent heat sources that redistribute the plasma and the neutral gas horizontally and vertically.…”
Section: Magnetosphere-ionosphere Interactionsmentioning
confidence: 84%
“…There exist some observational evidence, to suggest that some neutral density enhancements are associated with small-scale field-aligned current and Alfvénic waves causing ohmic heat in the plasma that is subsequently transferred to the neutral gas (Liu et al, 2010;. Lotko and Zhang (2018) examined Alfvénic heating effects in the cusp finding an increase in the F region Joule heating rate, which can be effective in heating the F region neutrals. Cusp neutral density enhancements associated with increased electron temperature, small-scale FAC, and vertical plasma motion are consistent with increased electron precipitation (e.g., Kervalishvili & Lühr, 2013;Lühr & Marker, 2013).…”
Section: Neutral Density Enhancements In the Polar Cuspmentioning
confidence: 99%
“…Since alternating electric fields keep velocity differences between neutrals and ions large, the mass density's time evolution may differ from what we presented above. Lotko and Zhang (2018) have shown that Joule heating rates generated by Alfvén waves are maximized at F layer altitudes, with the altitude profile depending on wavelength and frequency. In contrast, quasi-static electric fields maximize Joule heating rates at E layer altitudes.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%